Giant Optical Nonlinearities of Photonic Minibands in Metal–Dielectric Multilayers. Issue 11 (6th May 2020) - Acharyya, Jitendra Nath; Rao, D. Narayana; Adnan, Mohammad; Raghavendar, C.; Gangineni, R. B.; Prakash, G. Vijaya
Abstract : The giant nonlinear optical responses of photonic minibands of (Ag/SiO2 )4 metal–dielectric multilayers are reported using high intense femtosecond laser pulses. Ag and SiO2 alternative stack of layers form a series of coupled Fabry–Pérot resonators (Ag–SiO2 –Ag) and the cavity modes are split into transmission minibands in the metal reflective spectral region. The strong saturation of two‐photon absorption associated with multiphoton absorption (MPA) is observed at photonic miniband minimum (≈700 nm), whereas MPA is the strong dominant nonlinearity at peak maximum (≈725 nm). The metal‐cavity induced manifold enhancement (>10 3 times) in the Ag intrinsic nonlinearity follows wide miniband spectral (700–765 nm) trend. Results are discussed with respect to single (Ag/SiO2 )1 and bare Ag thin film results. The broad origin of giant nonlinearity is ascribed to the strong local cavity field enhanced metal interband transitions initiated by multiphoton absorption processes. The strong confinement of optical field and energy dissipation within these metal–dielectric coupled resonators are further evidenced by transfer matrix method simulations. The giant multiphoton absorptive type nonlinearities with very high laser‐damage threshold (≈50 GW cm −2 ) from these composite transparent metals are potentially beneficial for novel nonlinear optical limiters, optical Bragg coatings, and saturable optical absorbers for extremely high‐power ultrafast lasers operation. Abstract : The giant nonlinear optical responses from photonic minibands of (Ag/SiO2 )4 metal–dielectric multilayers are reported using high intense femtosecond laser pulses. The strong local cavity enhanced metal interband transitions and multiphoton absorption processes are involved. The giant nonlinearities with very high laser‐damage threshold from these composite transparent metals are potential for novel applications in extremely high‐power ultrafast laser operations.